Methods of Financial Literature Assessment: Kazakhstan’s Experience - K. Y. Khassenova; G. K. Ismailova; L. Z. Parimbekova; B. Kuantkan; N. M. Anarbekov (Экономика: стратегия и практика, 2022)
This research aims to study foreign experience and review the literature on methods for assessing financial literacy levels. Including analysis of financial literacy level in Kazakhstan based on official data from the AFRD. As a result, recommendations were developed for further improvement of the assessment methodology in Kazakhstan, based on the literature review. The research novelty lies in the systematization of the methods and approaches of various organizations and scientists to assess financial literacy in foreign countries. Additionally, development of recommendations for further improvement of financial literacy assessment based on foreign experience. Literature review results showed that many studies have standard features. Firstly, analysis of several factors may differ while the focus of their research interest. Secondly, the goal is to analyze t h e financial literacy of the population or specific groups of people. Secondary data analysis shows that financially illiterate citizens are inefficient participants in the securities market, have large debts, and use sources of financing irrationally. In terms of income – pensioners and youth. Therefore, there is a need for further development based on the experience of developed countries, where the level of financial literacy is high. The scientific significance of the work consists of the development of recommendations for improving the financial literacy of Kazakhstanis based on a methodological apparatus that considers integrated approaches and national restrictions. This is very important both for the theory and for the practice of further development of the state policy on improving the financial literacy of citizens of Kazakhstan.